Following Kohlberg : liberalism and the practice of democratic community - Reed, Donald R. C. (Revisions., 1997)
Most moral philosophers and psychologists have missed something crucial in the work of Lawrence Kohlberg (1927-87), best known for his theory of stages of moral development. In this comprehensive, useful volume, Donald R.C. Reed clearly illustrates how the Kohlbergian project has much to offer the crucial debate about moral psychology and how to revivify our society's jaded sense of fairness and responsibility. Psychologists, philosophers, theologians, educators, and therapists will find in this volume a comprehensive guide to Kohlberg's life work, a clear presentation of both theory and practice, and an understanding of moral maturity which encompasses both justice and responsiveness.